Using Guided Inquiry Learning with Multiple Representations to Reduce Misconceptions of Chemistry Teacher Candidates on Acid-Base Concept - Pikoli, Masrid (International Journal of Active Learning, 2020)
The aim of this study was to reduce misconceptions chemistry teacher candidates using guided inquiry learning with multiple representations. The study was carried out with the participation of a total of 69 chemistry teacher candidates at the chemistry department, State University of Gorontalo. Data were collected using three-tier diagnostic test with a 24-item test to solicit students misconceptions on the concept of acids and bases. Tests were given to another group of students at the same level and the coefficient of reliability (Cronbach's alpha) was 0.71. Validity of the tests have been evaluated by expert validator. The results showed that guided inquiry learning with multiple representations have succeeded to change students understanding into knowledge of correct concept..